2007
DOI: 10.1189/jlb.1006641
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of dendritic cell maturation and function by the Tax protein of human T cell leukemia virus type 1

Abstract: Human T cell leukemia virus type 1-associated myelopathy/tropical spastic paraparesis (HAM/TSP) is characterized by the generation of an intense CTL cell response directed against the viral transactivator protein Tax. In addition, patients diagnosed with HAM/TSP exhibit rapid activation and maturation of dendritic cells (DC), likely contributing to the robust, Tax-specific CTL response. In this study, extracellular Tax has been shown to induce maturation and functional alterations in human monocyte-derived DC,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
35
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(39 citation statements)
references
References 72 publications
3
35
1
Order By: Relevance
“…Because Tat-MoDC maturation can be blocked in the presence of anti-TNF-␣ and anti-TLR4 antibodies (data not shown), on the one hand, and can be stimulated by the N-terminal 1-45 fragment of Tat, on the other hand, our data suggest that MoDC maturation is primed by Tat action at the cell membrane level rather than following its uptake (37). Interestingly, HTLV-1 Tax protein, the equivalent of Tat protein in HIV-1, also induced MoDC maturation (72). Curiously, the activating effect of Tat protein seems to be counterbalanced by the action of Vpr, another HIV-1 regulatory protein, which has an antagonist effect on the maturation of DCs (73).…”
Section: Discussionmentioning
confidence: 60%
“…Because Tat-MoDC maturation can be blocked in the presence of anti-TNF-␣ and anti-TLR4 antibodies (data not shown), on the one hand, and can be stimulated by the N-terminal 1-45 fragment of Tat, on the other hand, our data suggest that MoDC maturation is primed by Tat action at the cell membrane level rather than following its uptake (37). Interestingly, HTLV-1 Tax protein, the equivalent of Tat protein in HIV-1, also induced MoDC maturation (72). Curiously, the activating effect of Tat protein seems to be counterbalanced by the action of Vpr, another HIV-1 regulatory protein, which has an antagonist effect on the maturation of DCs (73).…”
Section: Discussionmentioning
confidence: 60%
“…A total of 50,000 events collected for each sample were gated to , and 24 h) postinfection, cells were harvested for the isolation of total RNA (Qiagen, Valencia, CA) followed by treatment with DNase (rDNase I; Ambion, Inc., Austin, TX). The reverse transcription reaction was performed with 1 g of total RNA using Omniscript reverse transcriptase (4 U; Qiagen) in the presence of deoxynucleoside triphosphates (0.5 mM each deoxynucleoside triphosphate; Qiagen), oligo(dT) 15 primer (1 M; Promega, Madison, WI), and RNase inhibitor (10 U; Ambion). The kinetics of viral gene expression was examined by real-time PCR (RT-PCR) (ABI Prism 7700; Applied Biosystems, Foster City, CA).…”
Section: Generation Ofmentioning
confidence: 99%
“…Moreover, DCs cocultured with an HTLV-1-producing T-cell line were able to stimulate high levels of proliferation in autologous lymphocytes (28), as observed in HAM/TSP patients. HTLV-1 Tax protein also was shown to modulate DC maturation and function (1,2,15). Therefore, the importance of DCs in HTLV-1 pathogenesis is evident with respect to both ATL and HAM/TSP.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…DCs are also capable of transmitting the virus to T cells in vitro 41 . Jain et al showed that DCs exposed to the Tax protein become activated, leading to intense T-cell proliferation and inflammation due to their ability to present antigen to naïve T cells 42 . When evaluating the maturation of monocytederived DCs obtained from HTLV-1-infected individuals, Nascimento et al observed that DCs from healthy subjects displayed an activation profile (increased expression of costimulatory molecules and HLA-DR) absent in DCs from HTLV-1-infected patients 20 .…”
Section: Cytotoxic Cd8mentioning
confidence: 99%